2021
DOI: 10.2339/politeknik.672602
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Biodiesel Synthesis from Waste Cooking Oil in the Reactive Distillation Column Using Taguchi Methodology

Abstract: Bu makaleye şu şekilde atıfta bulunabilirsiniz(To cite to this article): Çağatay M. T., Çağatay Ş.ve Karacan S., "Optimisation of biodiesel synthesis from waste cooking oil in the reactive distillation column using taguchi methodology",

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Before proceeding to the control studies, the process was simulated with Aspen HYSYS to see the effects of feed inlet temperature, feed flow rate, mole ratio, reflux ratio and reboiler heat duty on temperature responses and FAME mole fraction. It was concluded that the simulation results were compatible with [35] in terms of the effect of the parameters. Accordingly, the most important parameters were determined as feed flow rate, mole ratio and reboiler heat duty.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Before proceeding to the control studies, the process was simulated with Aspen HYSYS to see the effects of feed inlet temperature, feed flow rate, mole ratio, reflux ratio and reboiler heat duty on temperature responses and FAME mole fraction. It was concluded that the simulation results were compatible with [35] in terms of the effect of the parameters. Accordingly, the most important parameters were determined as feed flow rate, mole ratio and reboiler heat duty.…”
Section: Discussionsupporting
confidence: 52%
“…Supportingly, similar results have been found in the literature. Likewise, the feed inlet temperature was not taken place in the model [35]. Accordingly, the most important parameter affecting the FAME mole fraction is the WCO flow rate, and the other significant one is the mole ratio.…”
Section: Results Of Simulation With Hysysmentioning
confidence: 99%
See 1 more Smart Citation